Маркетинг комуникациски микс во јавните институции во Република Македонија, компарирано со состојбата во Европската Унија - Стојановска, Ивана (Економски факултет, УКИМ, Скопје, 2018)
We live in times of rapid movement of information. Marketing communications are increasingly becoming part of the public sector institutions. If until recently it was characteristic only for promoting products, brands or businesses of the companies, modernity and desire to promote all the services provided by public institutions, contributed to the separation of the institutions separate budget for promotional activities. Trends are talking about massive use of marketing communications within the Public Institutions, special classes for this purpose or service obtained from a Marketing or PR Agency. Hence there is the need for planning of marketing communications mix, which covers the collection and use of information necessary for establishing the goals and strategies of the communications mix in Public Institutions. It is a continuous process of establishing and maintaining the reputation and the reputation of the Institution, which is to create mutual trust and understanding between the institution, the internal and external public. Recognizing the high risk of endangering the reputation and image and other repercussions with them brings everyday work, Public Institutions around the world and in the country are increasingly trying to create a communication plan for your work. This plan should be in accordance with the already established marketing purposes and in accordance with the needs of the target users and the current situation in the services market. Sometimes it is sufficient only one negative article in media, to put down a positive image, which can then last for years. The impact of media on public opinion is great and accordingly, with them is important to maintain continuous and good relations.
Marketing Communication Mix in Public Sector Institutions in Macedonia Compared to the Situation in the European Union
Докторска дисертација одбранета во 2018 година на Економскиот факултет во Скопје, под менторство на проф. д–р Нада Секуловска.
Keywords: marketing communications, publicity, communications, media, public institutions